Still undescribed bees in Europe—description of nine new European osmiine bee species (Hymenoptera, Megachilidae) - Müller, Andreas; Wood, Thomas J. (Zootaxa, 2025)
Bees of the tribe Osmiini (Megachilidae) are represented in Europe by about 250 described species. In this publication, nine additional European osmiine bee species are newly described and diagnosed: Heriades (Michenerella) clypeonitida sp. nov. from Spain, southeastern Europe and western Turkey, Hoplitis (Anthocopa) nevadensis sp. nov. and Hoplitis (Anthocopa) spinidorsa sp. nov. from the Sierra Nevada in southern Spain, Hoplitis (Hoplitis) cretensis sp. nov. from Crete, Hoplitis (Micreriades) andalusiae sp. nov. from southwesternmost Andalusia, Hoplitis (Micreriades) hispaniae sp. nov. and Hoplitis (Micreriades) fuscospina sp. nov. from central and southern Spain, Osmia (Helicosmia) inflatipes sp. nov. from Greece, and Osmia (Helicosmia) sardoa sp. nov. from Sardinia. For Hoplitis convolvuli Müller, 2022 (not Osmia papaveris convolvuli Ducke, 1899 = Osmia perezi Ferton, 1895), a replacement name is given: Hoplitis (Anthocopa) trabutiana nom. nov..